Endotoxin neutralization by an O-antigen specific monoclonal antibody: A potential novel therapeutic approach against Klebsiella pneumoniae ST258 - Szijártó, Valéria; Guachalla, Luis M.; Hartl, Katharina; Varga, Cecília; Badarau, Adriana; Mirkina, Irina; Visram, Zehra C.; Stulik, Lukas; Power, Christine A.; Nagy, Eszter; Nagy, Gábor (Virulence, 2017)
Klebsiella pneumoniae ST258 is a globally distributed multi-drug resistant pathogen responsible for severe invasive infections. In this study, the different virulence potential of K. pneumoniae ST258 isolates in endotoxin susceptible versus resistant animal models was shown. Furthermore, ST258 clinical isolates were found highly sensitive to the bactericidal effect of naive animal and human serum. These observations imply that LPS, released from the rapidly lysed bacteria, may contribute to the high mortality associated with ST258 bacteremia cases. A humanized version (mAb A1102) of a previously described murine mAb specific for the conserved LPS O-antigen, was tested for endotoxin neutralization. A1102 was able to neutralize TLR-4 activation by ST258-derived LPS in vitro with an efficacy exceeding that of polymyxin B by 3 orders of magnitude. Passive immunization with A1102 afforded a significant level of protection in a galactosamine-sensitized mouse model of endotoxemia, induced by ST258-derived LPS, or upon challenge with live bacteria. Efficacy was retained using an aglycosylated IgG, as well as upon complement depletion, suggesting that Fc-independent endotoxin neutralization may be the main protective mechanism in this model, in spite of the complement-dependent bactericidal and opsonic activities additionally observed for A1102 in vitro. Furthermore, rabbits that are naturally highly susceptible to endotoxin, were also significantly protected by low doses of A1102 when challenged with an ST258 strain. Given this unique mode of action and the high protective efficacy of this mAb, passive immunization, as prophylactic or adjunct therapeutic approach for the treatment of infections caused by ST258 isolates should be considered.